2022
DOI: 10.1007/s10639-022-11045-0
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model of second language writing strategies and their influence on anxiety, proficiency, and perceived benefits with online writing

Abstract: Second language (L2) writing strategies are essential for successful learning outcomes in courses with a substantial writing component and this is especially true during emergency remote teaching (ERT) when online writing tasks help compensate for the missing offline communication. Online writing tasks are multimodal and interactive, and widely delivered through assignment modules, discussion forums, social media, and other online channels, yet little is known pertaining to L2 writing strategies and online wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The students might have developed avoidance as an anxietycoping strategy over time as the study results indicated an increasing trend of avoidance behaviour as the year of study advanced. The gender effect has been a controversial issue in writing anxiety research as there are studies asserting no significant effects of gender (Mulyono et al, 2020;Quvanch & Na, 2022;Zerey, 2013), whereas there are also some studies suggesting higher levels of L2 writing anxiety for female learners (Bailey & Almusharraf, 2022;Cheng, 2002;Kırmızı et al, 2015;Keyvanoğlu & Atmaca, 2023). Regarding the year of study, similar results have been yielded in previous research (Cheng, 2002;Quvanch & Na, 2022;Mulyono et al, 2020), while few contradicting findings are also available (Ekmekçi, 2018).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The students might have developed avoidance as an anxietycoping strategy over time as the study results indicated an increasing trend of avoidance behaviour as the year of study advanced. The gender effect has been a controversial issue in writing anxiety research as there are studies asserting no significant effects of gender (Mulyono et al, 2020;Quvanch & Na, 2022;Zerey, 2013), whereas there are also some studies suggesting higher levels of L2 writing anxiety for female learners (Bailey & Almusharraf, 2022;Cheng, 2002;Kırmızı et al, 2015;Keyvanoğlu & Atmaca, 2023). Regarding the year of study, similar results have been yielded in previous research (Cheng, 2002;Quvanch & Na, 2022;Mulyono et al, 2020), while few contradicting findings are also available (Ekmekçi, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…It might, therefore, be interpreted that the students plan the content of their writing in Turkish and become demotivated and even panicked when they fail to find the exact English equivalent of the statement they create in Turkish. In a study which lends support to this interpretation, Bailey and Almusharraf (2022) found that the students using translation strategies, either using online translation tools or translating word-for-word by themselves, were those suffering the most from L2 writing anxiety. In a vicious circle, the more anxious the students felt, the more they resorted to translation tools.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…L2 writing anxiety is closely related to the use of L2 writing self-regulated strategies. Many studies demonstrated that students with low L2 writing anxiety could use more L2 writing self-regulated strategies (e.g., Asmari, 2013 ; Machida and Dalsky, 2014 ; Abolhasani et al, 2022 ; Bailey and Almusharraf, 2022 ). For example, Machida and Dalsky (2014) found that L2 writing strategies could help less anxious students more than those more anxious students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the need for further studies on L2 writing anxiety in terms of social, contextual, and learner variables has been emphasized in previous research (Bailey, Lee, Vorst, & Crosthwaite, 2017). Third, the role of blended and conventional writing environments (Bailey, Lee, Vorst, & Crosthwaite, 2017), emergency remote teaching (ERT) (Bailey & Almusharraf, 2022) and blog-mediated instruction (Fathi & Nourzadeh, 2019) in L2 writing anxiety has been foregrounded in relevant studies. Finally, there have been inconsistent research findings about the variables which play a role in L2 writing anxiety and writing performance of students (DeDeyn, 2011;Erkan & Saban, 2011;Negari & Rezaabadi, 2012;Singh & Rajalingam, 2012;Susoy & Tanyer, 2013;Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%